Psidium guajava leave-based magnetic nanocomposite γ-Fe2O3@GL: A green technology for methylene blue removal from water. Issue 6 (December 2019) - Abdulla, Noufal Komby; Siddiqui, Sharf Ilahi; Tara, Nusrat; Hashmi, Athar Adil; Chaudhry, Saif Ali
Graphical abstract: Highlights: Magnetic nanohybrid composite γ-Fe2 O3 @GL was developed for water purification. Maghemite nanoparticles were incorporated into framework of guava leaves. Prepared nanocomposite was highly functionalized. γ-Fe2 O3 @GL was efficient for adsorption of methylene blue. Methylene blue loaded γ-Fe2 O3 @GL was separated magnetically post adsorption. Abstract: This study reports the incorporation of magnetic γ-Fe2 O3 nanoparticles into the carbon framework of highly abundant, house hold medicinal plant, Psidium guajava, commonly known as Guava through co-precipitation. The prepared nanocomposite, γ-Fe2 O3 @GL was characterized with several spectroscopic and microscopic techniques, and showed the nano-porous structure having extensive oxygenous functional groups at the surface. The saturation magnetic moment of γ-Fe2 O3 @GL was found to be 0.72 emug −1 . Nanocomposite was used for the adsorption of methylene blue from water for which batch experiments were carried out under the change of various process parameters, and exhibited the fast and 99% removal of methylene blue from its solution having 10 mg L −1 concentrations with 1.0 gL −1 amount of γ-Fe2 O3 @GL. The maximum monolayer adsorption capacity was found to be in range 69.93 to 91.74 mgg −1, at 27–45 °C. The magnetically separable γ-Fe2 O3 @GL showed the high reusability and adsorption rate without significant loss after sixth adsorption-desorption cycles. Therefore, the prepared magnetic γ-Fe2 O3 @GL can be useful technique for water treatment having low cost and high adsorption capacity.